2013
DOI: 10.1007/s00535-013-0876-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mosapride on esophageal motor activity and esophagogastric junction compliance in healthy volunteers

Abstract: Mosapride at 40 mg augmented esophageal motor activities and reduced EGJ compliance in healthy volunteers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 40 publications
0
53
0
Order By: Relevance
“…In the present study, there was a tendency for mean LES pressure to increase following mosapride treatment, but the effect was not statistically significant. High‐dose mosapride has been reported to augment esophageal motor activities and reduce esophagogastric junction compliance in healthy volunteers . We suggest that, in this study, esophageal peristalsis may have provoked the hyperactive state without conditioning motility.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…In the present study, there was a tendency for mean LES pressure to increase following mosapride treatment, but the effect was not statistically significant. High‐dose mosapride has been reported to augment esophageal motor activities and reduce esophagogastric junction compliance in healthy volunteers . We suggest that, in this study, esophageal peristalsis may have provoked the hyperactive state without conditioning motility.…”
Section: Discussionmentioning
confidence: 53%
“…High-dose mosapride has been reported to augment esophageal motor activities and reduce esophagogastric junction compliance in healthy volunteers. 18 We suggest that, in this study, esophageal peristalsis may have provoked the hyperactive state without conditioning motility. High-dose mosapride may increase LES pressure significantly.…”
Section: Discussionmentioning
confidence: 54%
“…As expected, the least distensible locus was the EGJ, whereas the region 6-10 cm above the EGJ had higher distensibility, and the region 2-5 cm above the EGJ had the highest distensibility [39]. Looking into possible treatment options for GERD, Fukazawa et al [40] found that mosapride given intravenously augmented peristaltic contractions, increased LES pressure, and decreased EGJ distensibility.…”
Section: Gastroesophageal Reflux Diseasementioning
confidence: 78%
“…The EGJ distensibility was found to be unchanged in patients with Barrett's esophagus after radiofrequency ablation . Another study indicated that the intravenous administration of mosapride enhanced esophageal peristaltic contractions, increased LES pressure, and reduced EGJ distensibility . Based on these studies, more prospective data with long‐term follow‐up are needed to further investigate the role of FLIP in GERD and subsequent targeted surgical and endoscopic fundoplication procedures.…”
Section: Flip For Gerdmentioning
confidence: 96%